PENINGKATAN HASIL BELAJAR PKn MENGGUNAKAN MODEL ROLE PLAYING PADA PESERTA DIDIK KELAS V SDN O4: Bahasa Indonesia - Abdulah Abdulah (LPPM Universitas Muhammadiyah Muara Bungo, 2021)
This study began with the low PKn learning outcomes in V, teaching and learning activities are too dominated by teachers, many students are lazy about participating in the learning process, talking with their friends. This han an impact on low student learning interest so that ultimately student learning outcomes are less satisfying. This study aims to determine the result of civics learning in grade V students at SDN 04/II Jaya Setia at the year 2019/2020. This type of research is classroom action research, subjects of all fifth grade students at SDN 04/II Jaya Setia totaling 36 students. The technique of inferring the data in this with observation, learning achievement test sheets and documentation. The analysis technique used is qualitative and quantitative approaches. The results of the study using the role playing model showed an increase in each cycle for learning outcomes in cycle I namely 44% and 78% in cycle II. Then the learning process increased in cycle I, namely 74,9% and cycle II increased to 89,7%. Based on these data, it showa that the use of role playing can improve the process and learning outcomes of PKn in grade V SDN 04/II Jaya Setia.